Analisis Putusan Pengadilan Agama Tentang Hak hadhanah pada Mantan Suami - Yuli Yani (Bulletin of Community Engagement, 2024)
The object of this research study is to know how the judge's considerations in implementing the decision regarding hadhanah for ex-husbands at the Class 1A Tanjung Karang Religious Court. The method used in this study is to use a normative legal approach with qualitative literature (Library Research) and analytical nature. The data source in this study is secondary data by conducting a study of data sources in the form of legal materials, both in the form of primary legal materials, secondary legal materials, and tertiary legal materials, the data collection method is carried out by means of literature studies and documentation. Data processing is carried out by editing, coding, reconstructing, and constructing/systematizing. Data analysis using qualitative analysis with inductive thinking method. The result of this study is that the Religious Court Class 1A Tanjung Karang in deciding the case of hadhanah against a child who has not mumayyiz is given to the father. The Panel of Judges in considering its decision set aside Article 105 of the Compilation of Islamic Law. This is based on the Supreme Court Jurisprudence which contains the legal principle that child maintenance (hadhanah) is not absolute to the mother as in Article 105 letter (a) of the Compilation of Islamic Law but can be given to the father by considering the welfare of the child or the best interests of the child. Another consideration used by the Panel of Judges is by looking at the moral justice aspect of the child, because the child is comfortable and peaceful living with his father. When viewed from positive Indonesian law, the provision of hadhanah is appropriately given to the father, namely by considering the welfare and protection of the child.